1989
DOI: 10.1073/pnas.86.18.7290
|View full text |Cite
|
Sign up to set email alerts
|

Role of substance P in suppressing growth hormone release in the rat.

Abstract: To evaluate a possible physiological role of endogenous substance P (SP) in the control of growth hormone (GH; somatotropin) secretion, a specific antiserum against SP (anti-SP) was injected intraventricularly (3 I1 into the third cerebral ventricle) in unanesthetized unrestrained normal male rats. Control rats received an equivalent volume of normal rabbit serum (NRS). Intraventricular iniection of the NRS lowered plasma GH concentrations significantly. The lowering was detected on first measurement at 10 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Second, a number of investigators have demonstrated the presence of nerve fibers within the anterior pituitary gland of the rat. These nerve fibers are immunoreactive for factors involved in pituitary regulation, such as substance P (1,23,30), calcitonin gene-related peptide (12,22,23), somatostatin (23,35), and serotonin (26). Furthermore, these nerve fibers lie in contact with, or in close apposition to, somatotrophs (27,35), thyrotrophs (35), and corticotrophs (22,24,27), and some respond to changes in the overall hormonal state of the animal (e.g., increasing density of varicosities near corticotrophs after adrenalectomy) (22,24,27).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a number of investigators have demonstrated the presence of nerve fibers within the anterior pituitary gland of the rat. These nerve fibers are immunoreactive for factors involved in pituitary regulation, such as substance P (1,23,30), calcitonin gene-related peptide (12,22,23), somatostatin (23,35), and serotonin (26). Furthermore, these nerve fibers lie in contact with, or in close apposition to, somatotrophs (27,35), thyrotrophs (35), and corticotrophs (22,24,27), and some respond to changes in the overall hormonal state of the animal (e.g., increasing density of varicosities near corticotrophs after adrenalectomy) (22,24,27).…”
Section: Discussionmentioning
confidence: 99%
“…GHRH is known to increase Substance P in the pituitary ( 460 ). The significance of these findings is unknown but is intriguing considering that Substance P was found to be ineffective with respect to in vitro GH secretion ( 457 , 461 ).…”
Section: Autocrine Regulation Of Somatotrophsmentioning
confidence: 99%
“…Central administration of SP rapidly raised plasma GH in ovariectomized rats (Vijayan & McCann, 19796), and Kakucska & Makara (1983) also reported a stimulatory effect but only after deafferentation of the somatostatinergic input to the hypothalamus. However, more recent evidence suggests that centrally administered SP can also inhibit the release of GH in conscious rats (Arisawa, Snyder, De Palatis et al 1989), and a decrease (unconvincing) has been observed in primates (Eckstein et al 1980). These apparently contradictory results may be reconciled by the doses used and the influence of anaesthesia.…”
Section: Introductionmentioning
confidence: 97%